Enterprise Resource Planning, Organizational Factors and Organizational Performance - Massoud Egdair, Ibrahim Mohammed; Rajemi, M F; Nadarajan, Santhirasegaran (International Journal of Supply Chain Management, 2020)
In this previous study review, the approach of this paper will delve into the Organizational Factor (OF) towards Organizational Performance through adoption of Enterprise Resource Planning (ERP). To reduce the broad debate about these factors and their impact on the Organizational Performance especially when the organization trying to adopt new technology such as Enterprise Resource Planning (ERP). The current study tries to review and identify the study’s on organizational factors that affect the adoption of ERP and organizational performance